PEMIKIRAN FIQH WANITA QOSIM AMIN (Pusat Studi Gender dan Anak LPPM UIN Sunan Ampel Surabaya, 2013)
This paper explores Qasim Aminâs thinking on fiqh related to women; hijab, divorce, and polygamy.Initially, Qasim Amin wrote al-Mis riyyu>Â n to defend the patriarchal traditions that occurred in Egyptwhich is criticized by DâCouhourt. But, in five years later he wrote the book TahÂ ri> r marâah that reconstructsfiqin (Islamic jurisprudence) on womenâs issues. He reinforced his opinion in his later piece ofÂ writing titledal-marâah al-jadidah. There are several factors behind his shifting way of thinking; the influence ofmodernization in Egypt and the influence ofÂ French culture where he was studying. In social science theory,changing way ofÂ thinking is reasoneable and is in accordance with the theory ofÂ creative personality initiatedby David Mc.Celland.